2021
DOI: 10.3390/app11125702
|View full text |Cite
|
Sign up to set email alerts
|

Recent Updates on the Synthesis of Bioactive Quinoxaline-Containing Sulfonamides

Abstract: Quinoxaline is a privileged pharmacophore that has broad-spectrum applications in the fields of medicine, pharmacology and pharmaceutics. Similarly, the sulfonamide moiety is of considerable interest in medicinal chemistry, as it exhibits a wide range of pharmacological activities. Therefore, the therapeutic potential and biomedical applications of quinoxalines have been enhanced by incorporation of the sulfonamide group into their chemical framework. The present review surveyed the literature on the preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 107 publications
0
13
0
Order By: Relevance
“…Therefore, they are bacteriostatic and inhibit the growth and multiplication of micro-organisms. [15][16][17] SN derivatives are an important class of drugs used in clinics as pharmacological agents such as anti-bacterial, anti-tumor, anti-thyroid, anti-fungal, anti-inflammatory, anti-obesity, etc. [18] Recent use of SNs includes anti-cancer, antiviral HIV (HIV protease inhibitors, non-nucleoside HIV reverse transcriptase or HIV integrase inhibitors), [19][20][21] and Alzheimer's disease [22] agents.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they are bacteriostatic and inhibit the growth and multiplication of micro-organisms. [15][16][17] SN derivatives are an important class of drugs used in clinics as pharmacological agents such as anti-bacterial, anti-tumor, anti-thyroid, anti-fungal, anti-inflammatory, anti-obesity, etc. [18] Recent use of SNs includes anti-cancer, antiviral HIV (HIV protease inhibitors, non-nucleoside HIV reverse transcriptase or HIV integrase inhibitors), [19][20][21] and Alzheimer's disease [22] agents.…”
Section: Introductionmentioning
confidence: 99%
“…Quinoxaline derivatives have been established to have antifungal, antibacterial, and anticancer activities [27][28][29][30][31][32][33][34][35][36] . The combination of quinoxaline with Ag(I) ions results in the formation of complexes with fascinating biological characteristics, which could be an interesting alternatives to the current medications 37 .…”
Section: Introductionmentioning
confidence: 99%
“…A set of review articles emphasized on Ag(I) complexes with N-heterocycles has targeted their uses as anticancer agents against a variety of cancer cell lines. It has been found that several Ag(I) complexes have greater cytotoxicity than cis-platin with a relatively little poisonous effects to the healthy human cells [19][20][21][22][23][24][25][26] .Quinoxaline derivatives have been established to have antifungal, antibacterial, and anticancer activities [27][28][29][30][31][32][33][34][35][36] . The combination of quinoxaline with Ag(I) ions results in the formation of complexes with fascinating biological characteristics, which could be an interesting alternatives to the current medications 37 .…”
mentioning
confidence: 99%
“…Quinoxaline derivatives have been established to have antifungal, antibacterial, and anticancer activities 37 46 . The combination of quinoxaline with Ag(I) ions results in the formation of complexes with fascinating biological characteristics, which could be an interesting alternatives to the current medications 47 .…”
Section: Introductionmentioning
confidence: 99%